1999
DOI: 10.1034/j.1399-302x.1999.140401.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human papillomaviruses in the normal oral cavity of adults

Abstract: Human papillomavirus (HPV) infection in the normal oral cavity was studied by the sensitive polymerase chain reaction (PCR) using primers for the L1 region of human papillomavirus DNA and high fidelity amplification system. Cells were scraped from the oral mucosae of 7 (mean age; 42 years) and 30 (mean age; 32 years) volunteers with and without skin warts, respectively. Human papillomavirus DNA was detected in 30/37 (81.1%) specimens and their copy numbers per cell were 10(-1) to 10(-4) (mean, 10(-3)). The hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 36 publications
9
81
1
3
Order By: Relevance
“…Both HPV-16 and HPV-18 were found in one positive sample. A few reports also demonstrated that more than one type of HPV was detected in the oral cavity (Terai et al, 1999;Sosorbaram et al, 2006). Taken together, our data suggested that the nature of HPV infection may resemble other types of infection in that more than one strains of the same organism are able to reside in the oral cavity.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Both HPV-16 and HPV-18 were found in one positive sample. A few reports also demonstrated that more than one type of HPV was detected in the oral cavity (Terai et al, 1999;Sosorbaram et al, 2006). Taken together, our data suggested that the nature of HPV infection may resemble other types of infection in that more than one strains of the same organism are able to reside in the oral cavity.…”
Section: Discussionsupporting
confidence: 58%
“…Using quantitative PCR, a high prevalence of HPV has been reported in the normal oral cavity of adults. HPV DNA was detected in 30 of 37 (81.1%) specimens and their copy numbers per cell were 10-, 10-4 and 10-3 (Terai et al, 1999). Multiple HPV types were present in 17 of 30 (56.7%) specimens and 2 specimens contained HPV-16, -18 and other types.…”
Section: Enumeration Of Viral Copy Number By Real-time Pcrmentioning
confidence: 91%
See 1 more Smart Citation
“…Notwithstanding, the assessment of different methods used to detect HPV16 is important and fundamental in order to establish the etiological role of HPV in oral lesions. Table 1 shows HPV 16 prevalence in the normal oral mucosa in 16 results from 14 authors, by the SB, ISH and PCR detection methods, making up 56% of all the results, and this seems to depend on the population examined and the choice of method used to detect HPV 21,16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the normal oral mucosa we have seen a great variation in HPV rates detected, from 22% to 60% 17 ; from 0% all the way to 81.1% in studies using different methods, and with a limited number of individuals, and this seems to depend on the population studied and the choice of method 16,21 . It has been suggested that HPV prevalence in the normal mucosa includes subclinical and/or latent infections, and that the infection with a low number of virus copies is common in the oral cavity 8 .…”
Section: Human Papillomavirus Prevalence In Normal Oral Mucosamentioning
confidence: 98%